2019
DOI: 10.1007/s00259-019-04622-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of carotid artery atherosclerosis with PET: a systematic review

Abstract: Terms of use This work is brought to you by the University of Southern Denmark through the SDU Research Portal. Unless otherwise specified it has been shared according to the terms for self-archiving. If no other license is stated, these terms apply: • You may download this work for personal use only. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying this open access version If you believe that this document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 87 publications
1
16
0
Order By: Relevance
“…FDG) is a glucose analog that can be taken up by metabolically active tissues and its phosphorylation reaction can reflect the glucose metabolism of tissue cells. The uptake of [18F]FDG is directly proportional to the number of macrophages in high-risk plaques, which has been confirmed in histological studies with samples acquired by endarterectomy (59). So, PET/CT imaging of macrophages within carotid atherosclerosis plaque via [18F] FDG tracer has attracted significant attention from researchers.…”
Section: -Deoxy-2-[18f] Fluoro-d-glucose ([18f]mentioning
confidence: 81%
See 1 more Smart Citation
“…FDG) is a glucose analog that can be taken up by metabolically active tissues and its phosphorylation reaction can reflect the glucose metabolism of tissue cells. The uptake of [18F]FDG is directly proportional to the number of macrophages in high-risk plaques, which has been confirmed in histological studies with samples acquired by endarterectomy (59). So, PET/CT imaging of macrophages within carotid atherosclerosis plaque via [18F] FDG tracer has attracted significant attention from researchers.…”
Section: -Deoxy-2-[18f] Fluoro-d-glucose ([18f]mentioning
confidence: 81%
“…So, PET/CT imaging of macrophages within carotid atherosclerosis plaque via [18F] FDG tracer has attracted significant attention from researchers. Other studies using [18F] FDG-PET/CT have confirmed that [18F] FDG uptake is significantly correlated with macrophage content (56,59). To overcome the lack of specificity of the [18F] FDG tracer, both 3 ′ -dexoy-3 ′ [18F] fluorothymidine ([18F] FLT) and rHDL serving as markers of PET/CT imaging can target macrophage accumulation and activity in individuals with atherosclerosis (60,61).…”
Section: -Deoxy-2-[18f] Fluoro-d-glucose ([18f]mentioning
confidence: 99%
“…Therefore, NaF was proposed to detect microcalci cation as a sign of incipient atherosclerosis [21,25], which may not be as rapidly changing. In vitro and in vivo studies have demonstrate that arterial wall NaF uptake is due to adsorption to calcium deposits [26][27]. Likewise, high NaF uptake appears to be more consistently associated with different CVD risk factors [7].…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 99%
“…Non-invasive carotid imaging techniques, such as ultrasound (US), magnetic resonance imaging (MRI), positron emission tomography (PET) and computed tomography angiography (CTA), aim to characterize several morphological, functional or biochemical parameters associated with plaque ‘vulnerability’ and, thus, help estimate the risk of ischemic stroke [ 1 , 2 ]. Such parameters include the grade of stenosis, arterial wall remodelling, presence of a large lipid core and a thin fibrous cap, inflammation, intraplaque hemorrhage or neovascularization and nodular calcifications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%